Mid-Infrared Coherent Sources and Applications - Ebrahim-Zadeh, Majid; Sorokina, Irina T.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2008)
Coherent sources of mid-infrared (mid-IR) radiation are of great interest for a wide range of scienti?c and technological applications from spectroscopy and frequency metrology to information technology, industrial process control, pho- chemistry, photobiology and photomedicine. The mid-IR spectrum, which may be de?ned as wavelengths beyond ?2µm, covers important atmospheric windows, and numerous molecular gases, toxic agents, air, water, and soil pollutants, c- ponents of human breath, and several explosive agents have strong absorption ?ngerprints in this region. The development of practical coherent solid-state sources in the mid-IR can thus provide indispensable tools for a variety of - plications in environmental monitoring and pollution control, detection of water and soil contaminants, food quality control, agriculture and life sciences, and n- invasive disease diagnosis and therapy through breath analysis. Coherent mid-IR sources also offer important technologies for atmospheric chemistry, free-space communication, imaging, rapid detection of explosives, chemical and biological agents, nuclear material and narcotics, as well as applications in air- and sea-born safety and security, amongst many. The timely advancement of coherent mid-IR sources is, therefore, vital to future progress in many application areas across a broad range of scienti?c, technological, and industrial disciplines. On the other hand, more than 40 years after the invention of laser, much of the mid-IR spectrum still remains inaccessible to conventional lasers due to fun- mental limitations, most notably a lack of suitable crystalline laser gain materials.
Crystalline Laser and Nonlinear Optical Materials for the Mid-IR -- New Monocrystals with Low Phonon Energy for Mid-IR Lasers -- Orthorhombic Crystals of Lithium Thioindate and Selenoindate for Nonlinear Optics in the Mid-IR -- Quaternary Nonlinear Optical Crystals for the Mid-Infrared Spectral Range from 5 to 12 ?m -- Microstructured Semiconductors for Mid-Infrared Nonlinear Optics -- Sources in the Mid-IR -- Progress in Quantum Cascade Lasers -- High-Brightness 2.X ?m Semiconductor Lasers -- Broadband Mid-Infrared Solid-State Lasers -- New Regimes of Excitation and Mid-IR Lasing of Transition Metal Doped II–VI Crystals -- Advances in Mid-Infrared Fiber Lasers -- Mid-Infrared Optical Parametric Oscillators and Applications -- Mid-Infrared Integrated Optical Parametric Generators and Oscillators with Periodically Poled Ti:LiNbO3 Waveguides -- Optical Parametric Generators and Amplifiers -- Tunable THz Sources Based on Quasi-Phase-Matched Gallium Arsenide -- Semiconductor Waveguides for Nonlinear Frequency Conversion -- Applications -- Semiconductor Laser Based Trace Gas Sensor Technology: Recent Advances and Applications -- Trace Gas Analysis with Isotopic Selectivity Using DFG-Sources -- Photoacoustic Spectroscopy Using Continuous Wave Optical Parametric Oscillators -- Online Monitoring of Exhaled Breath Using Mid-Infrared Laser Spectroscopy -- Ultrabroadband Solid-State Lasers in Trace Gas Sensing -- Medical Applications of Mid-IR Solid-State Lasers -- Opportunities for Mid-IR Sources in Intense-Field and Attosecond Physics -- Ultrawideband Mid-Infrared Spectroscopy of Semiconductor Nanostructures.
Keywords: Engineering; Physical measurements; Measurement .; Solid state physics; Spectroscopy; Microscopy; Engineering, general; Measurement Science and Instrumentation; Solid State Physics; Spectroscopy and Microscopy